The effectiveness of spiritual therapy with emphasis on Islamic religious teachings on resilience, religious orientation and life satisfaction of divorced women - Sadati, Seyedeh Zahra; Mahdavi, Fatemeh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of investigating the effectiveness of spiritual therapy, emphasizing the teachings of Islam on resilience, religious orientation, and life satisfaction of divorced women. Methods: The current research was of the type of practical and quasi-experimental designs of pre-test-post-test and follow-up with a control group. The statistical population of this research included all divorced women of Sari city in the first six months of 2022. The sample of this research includes 30 people from the aforementioned community who were selected using available sampling method and were randomly included in an experimental group of spiritual therapy with an emphasis on the teachings of the religion of Islam based on the book of spiritual therapy and positive psychology approach (Safari- Nia, Mirmehdi and Sharifi, 2016) and Richards and Bergin (2005) spiritual interventions (with an Islamic approach (Arab Baferani, Kajbaf, and Abedi, 2012) and the control group was placed on the waiting list. The data using It was obtained from the religious orientation questionnaire of Allport and Ross (1950), the resilience scale questionnaire of Connor and Davidson (2003) and the life satisfaction scale of Diener, Emmons, Larsen and Griffin (1985). Variance was implemented with repeated measurement and SPSS-26 software. Results: The results showed that spiritual therapy with an emphasis on the religious teachings of Islam on resilience (F=10.83, P<0.001), life satisfaction (F=32.06, P<0.001), internal religious orientation (F=56.06, P<0.001), and external (F=35.26, P<0.001) divorced women was effective. Conclusion: Therefore, it can be concluded that spiritual therapy with vine Focusing on the teachings of Islam can be an effective intervention method to improve resilience, religious orientation and life satisfaction of divorced women.